2016
DOI: 10.7461/jcen.2016.18.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Onyx Embolization of Intracranial Pial Arteriovenous Fistula

Abstract: Intracranial pial arteriovenous fistulas (AVFs) are rare cerebrovascular lesions consisting of one or more arterial connections to a single venous channel without an intervening nidus. Because of the location and high flow dynamics of these lesions, neurosurgeons may have a difficulty deciding between endovascular treatment and open surgical treatment. We report on a patient who underwent endovascular treatment with liquid embolic agent. A 50-year-old man with a decreased mental state and a tonic seizure event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[10] Therefore, with the development of PAVF, other adverse consequences may have occurred, such as vasogenic edema [10] or hemorrhage. [11,12] Around the PAVF, there was no definite hemorrhage seen in the CT scan, but vasogenic edema was found in the DWI of our patient. It is difficult, however, to determine whether this edema was caused by neurosyphilis or PAVF.…”
Section: Discussionmentioning
confidence: 49%
“…[10] Therefore, with the development of PAVF, other adverse consequences may have occurred, such as vasogenic edema [10] or hemorrhage. [11,12] Around the PAVF, there was no definite hemorrhage seen in the CT scan, but vasogenic edema was found in the DWI of our patient. It is difficult, however, to determine whether this edema was caused by neurosyphilis or PAVF.…”
Section: Discussionmentioning
confidence: 49%
“…To our knowledge, only two reports of three patients with pial AVFs treated with Onyx embolization exist in the literature. 2,3 While Newman et al 3 used a balloon to achieve flow arrest in their two cases, no one has reported the use of such a flow-directed technique with the Scepter balloon in the cerebral circulation. The main advantages of this technique are:…”
Section: Discussionmentioning
confidence: 99%
“…For superficial lesions, either treatment may be possible, but endovascular treatment may be advantageous for deep or eloquent-area lesions, which are difficult to treat by direct surgery. According to several studies, [11][12][13][14] embolic materials used for endovascular treatment include balloons, coils, glue, polyalcohol, and Onyx. However, if the influx of an embolic material into a draining vein without complete shunt-point disconnection affecting venous outflow occurs, delayed hemorrhage may occur.…”
Section: Case Presentationmentioning
confidence: 99%